Persistence of Digestive Enzyme Activities of Sea Cucumber (Apostichopus japonicus): Evidence From Diet Switch After Evisceration - Li, Xueqi; Gao, Qinfeng; Tian, Yuan; Mei, Yaoping; Xu, Yuling; Cao, Yiming; Dong, Shuanglin; Zhou, Yangen; Sun, Yongjun; Ju, Wenming (Frontiers in Marine Science, 2022)
A two-stage diet-switch experiment was conducted to examine the hypothesis that the changes in digestive enzyme activities of sea cucumber (Apostichopus japonicus) induced by historic diets might persist in the regenerated intestines. In stage I, A. japonicus were treated with two different diets for 56 days, including diet A with 11% crude protein, 1% crude lipid, and 40% carbohydrate, and diet B with 18% crude protein, 2% crude lipid, and 35% carbohydrate. In stage II, each treatment was subjected to evisceration with 0.35M KCl or not (eviscerated and non-eviscerated groups), half of which were then switched to different diets from diet A to B or vice versa for 112 days. The persistence of digestive enzyme activities was evaluated by measuring the changes in digestive enzyme activities before and after evisceration. In stage I, diets B and A increased trypsin and amylase activities, respectively. In stage II, the higher trypsin activities were observed in eviscerated and non-eviscerated A. japonicus that had consumed diet B in stage I. The higher amylase activities were observed only in eviscerated A. japonicus that had consumed diet A in stage I. It indicated that the historic diets showed long-term effects on the digestion of A. japonicus, which led to the persistence of changes in both trypsin and amylase activities in intestines, especially in the regenerated intestines. In addition, the specific growth rates (SGRs) and metabolic rates (MRs) of A. japonicus were affected by the long-term effects of historic diets. Meanwhile, the relationships between enzymic activities, SGRs, and MRs were observed in A. japonicus, indicating that the historic diets could produce long-term effects on the growth and metabolism of A. japonicus through their long-term effects of historic diets on digestive enzyme activities. In conclusion, the present study showed that the changes in digestive enzyme activities induced by different diets in stage I could persist in the intestines and regenerated intestines, leading to long-term effects of historic diets on the growth and metabolism of A. japonicus.